Bulevirtide monotherapy in patients with chronic HDV: efficacy and safety results through week 96 from a phase III randomized trial - Wedemeyer, Heiner; Aleman, Soo; Brunetto, Maurizia; Blank, Antje; Andreone, Pietro; Bogomolov, Pavel; Chulanov, Vladimir; Mamonova, Nina; Geyvandova, Natalia; Morozov, Viacheslav; Sagalova, Olga; Stepanova, Tatyana; et al. (Journal of hepatology, 2024)
Background & Aims - Bulevirtide (BLV), a first-in-class entry inhibitor, is approved in Europe for the treatment of chronic hepatitis delta (CHD). BLV monotherapy was superior to delayed treatment at week (W) 48, the primary efficacy endpoint, in the MYR301 study (NCT03852719). Here, we assessed if continued BLV therapy until W96 would improve virologic and biochemical response rates, particularly among patients who did not achieve virologic response at W24. - Methods - In this ongoing, open-label, randomized phase III study, patients with CHD (N = 150) were randomized (1:1:1) to treatment with BLV 2 mg/day (n = 49) or 10 mg/day (n = 50), each for 144 weeks, or to delayed treatment for 48 weeks followed by BLV 10 mg/day for 96 weeks (n = 51). Combined response was defined as undetectable hepatitis delta virus (HDV) RNA or a decrease in HDV RNA by ≥2 log10 IU/ml from baseline and alanine aminotransferase (ALT) normalization. Other endpoints included virologic response, ALT normalization, and change in HDV RNA. - Results - Of 150 patients, 143 (95%) completed 96 weeks of the study. Efficacy responses were maintained and/or improved between W48 and W96, with similar combined, virologic, and biochemical response rates between BLV 2 and 10 mg. Of the patients with a suboptimal early virologic response at W24, 43% of non-responders and 82% of partial responders achieved virologic response at W96. Biochemical improvement often occurred independently of virologic response. Adverse events were mostly mild, with no serious adverse events related to BLV. - Conclusions - Virologic and biochemical responses were maintained and/or increased with longer term BLV therapy, including in those with suboptimal early virologic response. BLV monotherapy for CHD was safe and well tolerated through W96. - Impact and implications - In July 2023, bulevirtide was fully approved for the treatment of chronic hepatitis delta (CHD) in Europe based on clinical study results from up to 48 weeks of treatment. Understanding the efficacy and safety of bulevirtide over the longer term is important for healthcare providers. In this analysis, we demonstrate that bulevirtide monotherapy for 96 weeks in patients with CHD was associated with continued improvements in combined, virologic, and biochemical responses as well as liver stiffness from week 48 at both the 2 mg and 10 mg doses. Patients with suboptimal virologic responses to bulevirtide at week 24 also benefited from continued therapy, with the majority achieving virologic response or biochemical improvement by week 96. - Clinical Trials.gov identifier - NCT03852719